Weighted Family History Density of Substance Use: Influence on Participant Substance Use Onset, Duration, and Escalation - Litteral CA; Martel MM; Mattingly DT; Moore JX (Substance Abuse and Rehabilitation)
Carleigh A Litteral,1,2 Michelle M Martel,1 Delvon T Mattingly,2,3 Justin Xavier Moore2,3 1Department of Psychology, University of Kentucky, Lexington, KY, USA; 2Markey Cancer Center, University of Kentucky, Lexington, KY, USA; 3Center for Health, Engagement, and Transformation (CHET), Department of Behavioral Science, University of Kentucky, Lexington, KY, USACorrespondence: Carleigh A Litteral, University of Kentucky, College of Arts & Sciences, Kastle Hall, 503 Library Drive, Room 111I, Lexington, KY, 40506, USA, Tel +15029632067, Email carleigh.litteral@uky.eduPurpose: This study investigates how weighted family history density (WFHD) influences the intergenerational transmission of substance use disorders (SUDs), focusing on onset, escalation, and duration of substance use. Substance preference concordance and sex-specific links between affected family members and participants were also assessed.Methods: A cross-sectional analysis of the National Epidemiological Survey on Alcohol and Related Conditions III (NESARC-III) included 36,309 adults. WFHD was defined as drug or alcohol problems among first- and second-degree relatives. Linear regression models assessed the relationships between WFHD, age at onset, and duration of substance use, adjusting for sociodemographic factors. The escalation period to peak alcohol use was plotted by WFHD level, and correlation analyses examined the role of affected family members in shaping participant substance preferences and sex-stratified SUD diagnoses.Results: Each unit increase in WFHD was linked to a minimum 0.53-year earlier onset [β = − 0.53, SE = 0.02] and 0.48-year longer duration (β = 0.48, SE = 0.03) of substance use. WFHD increased the adjusted odds of onset before age 18 by 27% and duration exceeding half of one’s age by 19%. Adjusted odds for durations exceeding 5 and 10 years rose by 26% and 21%, respectively. Higher WFHD was linked to faster escalation to peak use. Substance preferences showed significant concordance within families. Males were most strongly associated with paternal use, while females were more closely linked to maternal use.Conclusion: Higher WFHD is strongly associated with earlier initiation, faster escalation to peak use, prolonged duration of substance use, and patterns of substance preference concordance, highlighting the importance of including family history assessments in substance use prevention and intervention strategies. Future research should use longitudinal studies to establish causal relationships and explore interactions between WFHD and other risk factors, such as environmental stressors, epigenetic changes, or genetic markers.Plain Language Summary: &#x2003Why This Study Was Done: People with family members who have experienced alcohol or drug problems are at a higher risk of developing substance use problems themselves. This study measures that risk using Weighted Family History Density (WFHD), which considers how many close and extended family members have struggled with substance use.What the Study Found: Using data from over 36,000 adults in the National Epidemiological Survey on Alcohol and Related Conditions-III (NESARC-III), we explored whether higher WFHD is linked to earlier onset, longer duration, and faster escalation to peak substance use. We also examined whether familial substance use patterns differed by sex and whether people’s substance choices aligned with those of their family members.What the Results Mean: Our results show that higher WFHD is associated with earlier substance use, longer duration, and faster escalation to peak use. Substance preferences often matched those of their family members. Correlation analyses showed that males with substance use disorders had stronger correlations with affected fathers, while females had stronger correlations with affected mothers.Why This Is Important: These results highlight the importance of considering family history in substance use prevention and treatment. Identifying individuals at high familial risk could aid in developing early interventions to delay or reduce substance use and inform and help connect those at risk with treatment resources before their condition escalates. Future studies should explore the biological and environmental mechanisms behind these patterns to develop more effective prevention strategies.Keywords: substance use disorder, addiction, predisposition, genetic, environment, inheritance